Biogeographic, Driving Factors, Assembly, and Co-occurrence Patterns of Archaeal Community in Biocrusts - Li, Yuanlong; Wei, Jingyi; Yang, Haijian; Zhang, Delu; Hu, Chunxiang (Frontiers in Microbiology, 2022)
Archaea exhibit strong community heterogeneity with microhabitat gradients, and are a nonnegligible part of biocrust's microorganisms. The study of archaeal biogeography in biocrusts could provide new insights for its application in environmental restoration. However, only a few studies on assembly processes and co-occurrence patterns of archaeal community in patchy biocrusts have been reported, especially considering the number of species pools. Here, we comprehensively collected biocrusts across 3,500 km of northern China. Different successional biocrusts from various regions contain information of local climate and microenvironments, which can shape multiple unique archaeal species pools. The archaeal community differences in same successional stage exceeded the variations between successional stages, which was due to that the heterogeneous taxa tended to exchange between unknown patches driven by drift. We also comparatively studied the driving forces of community heterogeneity across three to ten species pools, and assembly and co-occurrence patterns were systematically analyzed. The results revealed that the impact of spatial factors on biogeographic patterns was greater than that of environmental and successional factors and that impact decreased with the number of species pools considered. Meanwhile, community heterogeneity at phylogenetic facet was more sensitive to these driving factors than taxonomic facet. Subgroups 1 (SG1) and 2 (SG2) of the archaeal communities in biocrusts were dominated by Nitrososphaeraceae and Haloarchaea, respectively. The former distribution pattern was associated with non-salinity-related variables and primarily assembled by drift, whereas the latter was associated with salinity-related variables and primarily assembled by homogeneous selection. Finally, network analysis indicated that the SG1 network had a higher proportion of competition and key taxa than the SG2 network, but the network of SG2 was more complex. Our study suggested that the development of archaeal community was not consistent with biocrusts succession. The dominant taxa may determine the patterns of community biogeography, assembly and co-occurrence.